Evaluation of Diagnostic Value of FAST in Patients with Multiple Trauma referring to a Trauma Center in Northern Iran - Iraj Baghi; Arghavan Malekshahi; Mohammadreza Mobayen; Mohammadsadegh Mousavi (Novelty in Clinical Medicine, 2022)
Background: Abdominal injuries are among the most common causes of death in trauma patients, one-third of whom develop abdominal trauma. Focused assessment with sonography is a part of the initial examination for emergency care of patients with abdominal blunt trauma.Objectives: This study aimed to investigate trauma patients with positive FAST under laparotomy surgery in a Trauma Center.Methods: This cross-sectional study was conducted on 180 patients with abdominal trauma admitted to Poursina Hospital, Rasht, Iran between 2016 and 2017. On admission, they were examined with FAST and divided into positive and negative. The patients underwent laparotomy/CT after physical examinations, and their results were mentioned as negative/positive.Results: Sensitivity, specificity, positive and negative predictive values of FAST compared with CT-scan in all patients were 60%, 52.4%, 23.3% and 84.4%, respectively. Seventy-eight out of 90 patients with positive FAST underwent laparotomy and 19 patients with negative FAST underwent laparotomy. Low blood pressure, GCS, and the hospital arrival time had a significant relationship with the likelihood of false positives of FAST compared to CT scans, whereas the significant relationship was reported only in false-negative cases in age. There was a relationship between false-positive cases of the FAST compared with laparotomy in blood pressure. This relationship was significant in the case of false-negative cases in age (P<0.05).Conclusion: Implementing FAST by surgical assistants does not have high sensitivity and specificity. Therefore, it is recommended to use other diagnostic methods such as CT-scan along with FAST, besides paying attention to sufficient training of surgical assistants in performing FAST.